2020
DOI: 10.1097/mat.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated Heparin Versus Subcutaneous Nadroparin in Adults Supported With Venovenous Extracorporeal Membrane Oxygenation: a Retrospective, Multicenter Study

Abstract: Extracorporeal membrane oxygenation (ECMO) requires constant management of coagulation. Whereas unfractionated heparin remains the anticoagulant of choice, experienced centers report high bleeding rates. Biocompatibility of the extracorporeal circuit enables management of anticoagulation with subcutaneous low-molecular-weight heparins only. The aim of this study was to evaluate the safety and feasibility of anticoagulation with subcutaneous nadroparin compared with unfractionated heparin during respiratory ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Only two direct comparisons are currently available on the safety and efficacy of low-molecular-weight vs. unfractionated heparin during extracorporeal oxygenation. While Piwowarczyk et al ( 15 ) noted similar rates of thromboembolic events and bleeding complications for nadroparin and unfractionated heparin, these findings might not be directly relatable to ours, since the comparability of enoxaparin and nadroparin has been questioned ( 32 ). Our own study group observed, in perioperative settings of lung transplantation, bleeding events with enoxaparin in 12.5% and with unfractionated heparin in 22.7% of patients ( p = 0.31) ( 13 ).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Only two direct comparisons are currently available on the safety and efficacy of low-molecular-weight vs. unfractionated heparin during extracorporeal oxygenation. While Piwowarczyk et al ( 15 ) noted similar rates of thromboembolic events and bleeding complications for nadroparin and unfractionated heparin, these findings might not be directly relatable to ours, since the comparability of enoxaparin and nadroparin has been questioned ( 32 ). Our own study group observed, in perioperative settings of lung transplantation, bleeding events with enoxaparin in 12.5% and with unfractionated heparin in 22.7% of patients ( p = 0.31) ( 13 ).…”
Section: Discussioncontrasting
confidence: 61%
“…Current guidelines recommend the use of unfractionated heparin for anticoagulation during extracorporeal membrane oxygenation (ECMO) (12). Standardized protocols using low-molecularweight heparin have yet to find their way into routine clinical practice, even though promising data have been presented for enoxaparin and nadroparin (13)(14)(15). There are also reports on major advantages of low-molecular-weight over unfractionated heparin like reduced bleeding complications or heparin-induced thrombocytopenia (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Despite paucity of literature related to anticoagulation management based on LMWH only during ECMO support, [2][3][4] we decided to introduce this approach since the second wave of Coronavirus disease 2019 (COVID-19) pandemic, to simplify and standardize anticoagulation management, reducing the strain on the team members, particularly on most recently recruited, and less experienced ones, involved to expand ECMO capacity.…”
Section: To the Editormentioning
confidence: 99%
“…According to our center’s experience before the COVID-19 pandemic, anti-Xa guided subcutaneous nadroparin was used for anticoagulation during ECMO support. 13 This mode of anticoagulation during ECMO, although performed by less than 4% of centers, has been reported to be feasible and safe in observational trials and case series. 14 , 15 …”
Section: Anticoagulation Bleeding and Thrombotic Complicationsmentioning
confidence: 99%